Adaptasi strategi bank syariah di tengah arus regulasi dan inovasi keuangan global - Saputra, Lubbul Hikam (Maliki Interdisciplinary Journal, 2025)
The development of global financial regulations and digital innovation requires Islamic banks to implement responsive and sustainable adaptation strategies. This study aims to analyze the strategic adaptation of Islamic banks in facing the flow of international regulations and global financial innovation, particularly in digital service transformation, collaboration with fintech, and the strengthening of Sharia-based internal regulations. The research employs a descriptive qualitative approach through a literature review of five academic journals published between 2020 and 2024. The findings reveal that Islamic banks have adopted three major adaptive strategies: (1) Islamic value-based digital transformation, (2) internal regulatory frameworks aligned with global financial standards, and (3) the enhancement of human resources that are technologically literate while maintaining Sharia compliance. These adaptive strategies play a vital role in maintaining competitiveness, operational stability, and institutional credibility amid regulatory pressures and the rapid growth of financial technology. The study contributes both theoretical and practical insights for developing Islamic banking policies in Indonesia.